Synergistic interaction between trimetazidine and ketoprophen in mice - Daniela Carmen Ababei; Sorin Beşchea; Monica Neamţu; A. Vasincu,; Oana Arcan; Veronica Bild (Medicamentul Veterinar, 2015)
Recent studies have demonstrated the antinociceptive, anti-inflammatory, and gastric protective effects of trimetazidine (TDZ) on various models in rats. The present study proposes to demonstrate the antinociceptive action in mice, evaluated in conditions of inflammatory pain, together with the determination of the type of pharmacodynamic interaction between trimetazidine and ketoprofen (KETO). In this study we used as experimental model of nociception the abdominal constrictive response (writhing test), induced with Zymosan A in mice, and for the study of the interaction we used as quantitative evaluation method the method of binary combinations in fixed proportions. The experimental results allowed the demonstration of the ED 50 for ketoprofen (DE50 = 0.606 ± 0.108 mg/kg) and the demonstration of the synergism for the associated substances. (Zadd = 1.818 ± 0.326 mg/kg, Zmix = 0. 458 ± 0.101 mg/kg, γ = 0.251, Tc = 4.928, Tt = 3.84, P< 0.05). The results demonstrate that for the same level of activity (50%), smaller doses of each substance can be used, compared to the doses of the substances administered alone, which might contribute to a reduction in the number or severity of adverse effects. on the other side, the demonstration of the synergism might contribute to the clarification of the action mechanisms. The experiments presented below were made in agreement with the rules and regulations concerning the work with lab animals.